Hukum Tentang Orang (Perbandingan Antara KUH Perdata Indonesia, Inggris Dan Amerika) - Rizki Nurdiansyah; Muhammad Adam Damiri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
The law of persons is an important aspect of a country's legal system that regulates the status, rights and obligations of individuals. In this study, we will compare the legal treatment of persons in the Indonesian, British and American Civil Codes. This comparative analysis will cover several aspects,including the legal status of persons, personal rights, and legal obligations relating to individuals. The comparison begins by looking at the legal status of people within the three legal systems. The Indonesian Civil Code recognizes a person's legal status based on nationality, age, and legal capacity. In the UK, the legal status of a person is determined by nationality and citizenship status, whereas in the United States, the legal status of a person relates to citizenship, nationality and immigration status. The abstract is short, about 150-200 words, written with the size of 10. The abstract should be informative and briefly described the research background (review), research purposes, research method, main results, and main conclusion. The abstract is often presented separately from the complete script, so it must be able to stand on itself. The library is not allowed to be listed in the abstract, but if it is important then the citation refers only to the name of the first author and the year. The abstract is written in Indonesian and English. In this overall comparison, it was found that although there are differences in legal approaches to persons in the Indonesian, British and American Civil Codes, there are also some similarities in the protection of individual rights. Universal legal principles such as liberty, human rights and legal responsibility remain the cornerstone of these three legal systems. Further research on this comparison can provide deeper insights in understanding legal protection for individuals in different contexts